Sweden : Financial Sector Assessment Program Update: Technical Note on Stress Testing of the Banking Sector. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Although Sweden has recovered from the financial crisis, authorities have already initiated exit measures from crisis response policies. The Financial Sector Assessment Program (FSAP) Update undertook a financial stability analysis of the banking sector, including a comprehensive stress-testing exercise of banks' solvency and liquidity positions. While the banking sector appears resilient to credit risk stress tests, liquidity stress test results reveal some weaknesses owing to its heavy reliance on wholesale funding. Swedish bank groups have extensive cross-border activities, mostly in the Scandinavian and Baltic regions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet